Teacher's Understanding Level In Describing The Profile Of Pancasila Students - Sulastri, Sulastri; Nurdiyana, Nurdiyana (Cita konsultindo, 2024)
One form of implementation of the Pancasila student profile is students who always practice Pancasila values such as devotion to God Almighty by carrying out worship according to their religion. Teachers as the spearhead of implementing learning have a big role in guiding and focusing students. The mentoring process carried out by teachers is not only related to intellectuality but also strengthening personality learning, one of the things that is in the spotlight in the world of learning and especially for teachers is improving students' morals and morals. In learning, teachers also have an important role in shaping students' personalities at school. Teachers are reliable educators who have the main task of educating, teaching, guiding, focusing, training, calculating and evaluating students. The level of understanding of teachers in realizing the Pancasila student profile must be increased because of the 6 indicators of implementing the Pancasila student profile, not all of them have been fully implemented by teachers. The first indicator, namely Faith, Devotion to God Almighty and having noble morals, was achieved by 95%, Global Diversity by 73%, mutual cooperation by 90%, creativity by 91%, critical reasoning by 71%, and independence by 58%. The inhibiting factor in implementing the Pancasila profile which is integrated with the module is that many teachers have not participated in intensive Merdeka curriculum training so that understanding in integrating the six elements of the Pancasila student profile into learning tools has not been fully implemented.